Peran Stakeholder Dalam Mendukung Sempadan Tukad Badung Sebagai Sarana Leisure And Recreation Masyarakat Kota Denpasar - Fahrul, Fahrul; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
Urban society is synonymous with high levels ofstress. One of the activities that made the citizens in relieving stress and boredom of the mind is a leisure and recreation activity like in border of Tukad Badung. Denpasar City Government seeks to improve the Tukad Badung border area in various ways but until now still not optimal. Another stakeholders tried to improve the  border of Tukad Badung for better and could be developed into a leisure and recreation suggestion for the citizens Each stakeholder certainly has different roles in accordance with the competence and ability. It is interesting how the role of each stakeholder. The research method used in this research is qualitative research. Where qualitative research used in-depth interview technique, observation and qualitative documents and also used the role concept to reviewing the research. The result of the research showed that stakeholders from the government consist of Banjar Gelogor Carik, Desa Pemogan, Dinas Pariwisata Kota Denpasar, Dinas Pekerjaan Umum Denpasar And Balai Wilayah Sungai Bali-Nusa Penida. While the stakeholder of the community consists of Kelompok Bank Sampah Pemogan Dan Komunitas Kali Bersih Pemogan. All these stakeholders have their respective roles in maintaining and expanding the badung border ropes in the path of the fishing pole, pemogan. Despite having different roles but all the stakeholders are hand in hand to realize the tidal river borders that are neat, beautiful and clean.   Keywords : stakeholders role, leisure and recreation, citizens, borders of Tukad Badung